The Effectiveness of Weekly Online-Based Quizzes on English Test Scores in 8th Grade Students at SMPN 1 Mataram - Sari, Ika Permata; Amin, Muhammad; Junaidi, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Online-based quizzes have been widely used to enhance student learning outcomes, but their impact on test performance in 8th grade has not been thoroughly examined. This study aims to investigate the effectiveness of weekly online-based quizzes in improving the test scores of 8th-grade students at SMPN 1 Mataram. A quantitative pre-test and post-test design was implemented with 30 participants. The findings revealed a significant improvement in students’ test scores, supporting the integration of online-based quizzes as a tool to enhance learning outcomes.